2018
DOI: 10.21873/invivo.11353
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Bone Augmentation Using Three-dimensionally Printed Cap in the Rat Calvarial Partial Defect

Abstract: The results clearly showed that this system was successful for VBA in a research animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…There are several animal models widely used for the assessment of HA substitutes on bone reconstruction (as reviewed in Reference [180]). For flat bone reconstruction, the most common is the calvarial defect model, which is frequently tested in small rodents: rat [181,182] and rabbits [183]. Long bone reconstruction uses a distraction osteogenesis model—a surgical model that creates a gap in a long bone (usually tibia), using continuous traction on the osteotomy ends.…”
Section: Efficacy Evaluation Of Cap-based Bioceramicsmentioning
confidence: 99%
“…There are several animal models widely used for the assessment of HA substitutes on bone reconstruction (as reviewed in Reference [180]). For flat bone reconstruction, the most common is the calvarial defect model, which is frequently tested in small rodents: rat [181,182] and rabbits [183]. Long bone reconstruction uses a distraction osteogenesis model—a surgical model that creates a gap in a long bone (usually tibia), using continuous traction on the osteotomy ends.…”
Section: Efficacy Evaluation Of Cap-based Bioceramicsmentioning
confidence: 99%
“…Histological observations indicated that the new bone does not touch the shell, thereby avoiding problems related to the separation of the samples from the shells. In addition, 3D printing technology has been successfully applied to the design of the VGBR animal model (40,49,99), which may considerably reduce the time and cost compared with traditional casting metal barrier shells. The calvaria onlay model is commonly used to compare and detect different block bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The shell is then filled with biomaterials and fixed to the rat calvaria directly using screws via an anchor ring (30,40,43) or placed on a circular groove (27)(28)(29) that is made on the rat calvaria using a trephine under profuse irrigation with sterile saline. As the rat calvaria is thin, care should be taken not to damage the endocranium.…”
Section: Different Experimental Models Of Vertical Bone Augmentationmentioning
confidence: 99%
“…The calvarial bone defect rat model was established as described in previous studies [ 22 , 23 ] with a few modifications. Briefly, the rats were intraperitoneally anaesthetized with alpha chloralose (55 mg/kg).…”
Section: Methodsmentioning
confidence: 99%